2019
DOI: 10.1371/journal.pone.0220082
|View full text |Cite
|
Sign up to set email alerts
|

A case of silent invasion: Citizen science confirms the presence of Harmonia axyridis (Coleoptera, Coccinellidae) in Central America

Abstract: Harmonia axyridis (Coleoptera, Coccinellidae) is a globally invasive ladybird. It has been intentionally introduced in many countries as a biological control agent, whereas it has been unintentionally released in many others. Climatic factors are important in limiting the spread of H . axyridis . For example, very few records are known from tropical or desert regions. Currently, no published reports are known from Central America. Here, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 55 publications
0
54
0
Order By: Relevance
“…Ameixa et al 2019;Brown et al 2008;Koch and Galvan 2008), but detailed analysis of the distribution of the species in most of the countries in South America is rather outdated or scarce (but see Grez et al 2016;Hiller and Haelewaters 2019). The species was introduced as a biological control agent through the 1980s and 1990s (Grez et al 2016), and to date wild populations have been reported except in Bolivia, French Guiana, Guyana and Suriname (Brown et al 2011;Camacho-Cervantes et al 2017;Hiller and Haelewaters 2019;Montero and Vignaroli 2008;Olave 2016 and see Online Resource 1 for more details). However, the magnitude of its expansion in the countries where it is present has only been studied in Chile, where it shows a continuous distribution from * 29°S to * 42°S, being absent only in the northern desert and in southern Patagonia (Grez et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ameixa et al 2019;Brown et al 2008;Koch and Galvan 2008), but detailed analysis of the distribution of the species in most of the countries in South America is rather outdated or scarce (but see Grez et al 2016;Hiller and Haelewaters 2019). The species was introduced as a biological control agent through the 1980s and 1990s (Grez et al 2016), and to date wild populations have been reported except in Bolivia, French Guiana, Guyana and Suriname (Brown et al 2011;Camacho-Cervantes et al 2017;Hiller and Haelewaters 2019;Montero and Vignaroli 2008;Olave 2016 and see Online Resource 1 for more details). However, the magnitude of its expansion in the countries where it is present has only been studied in Chile, where it shows a continuous distribution from * 29°S to * 42°S, being absent only in the northern desert and in southern Patagonia (Grez et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1a, Online Resource 2, Table 2a). Recently, Hiller and Haelewaters (2019) mapped the distribution of H. axyridis in Central and South America using Flickr, iNaturalist, and museum records. For Argentina, they found 24 records in Flickr (dated from 2006 to 2016) and 89 records in iNaturalist from which only 19 had been uploaded before the promotion of our project and only 15 represented independent points (four of them were duplicates).…”
Section: Introductionmentioning
confidence: 99%
“…US populations are almost monomorphic in the pattern of elitraes with the succinea phenotype [22,40]. Beetles of the conspicua phenotype were found in Denver with a frequency of less than 1% [41] [38]. In the southwestern state of Oregon, the proportion of this phenotype in nature was 1.4%; in the same state, the only specimen of the spectabilis phenotype was found from almost 3,000 beetles of the biocontrol line imported from Japan [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Harmonia axyridis is an interesting model species as it has been considered to be one of the most invasive insect species in Europe and North America 32,33 . Harmonia axyridis is native to Asia, particularly to areas with a temperate and subtropical climate 34 , but has recently spread to many European countries, North and South America and some African countries [35][36][37] . The speed of their range expansion in a novel environment has been extremely fast because in 15 years (2000-2015), the species spread over almost the whole of Europe 34,38 .…”
mentioning
confidence: 99%